Surviving the taughest race on earth - Dugard, Martin (McGraw-Hill, 1998)
Adventure, danger, and exotic places are at the heart of the most difficult race in the world. International teams battle time, the elements, and physical and emotional exhaustion in some of the wildest landscapes on the planet from the jungles of Borneo to the peaks of the Andes. Only a fraction of the competing teams are able to finish a typical adventure race, as fatigue and injuries take a continual toll. This book is a dramatic, fascinating and intensely personal story of a journalist who has been covering adventure racing from its early days, both as a reporter and a competitor.